Dancing Carvings: Intermedial Transformation of Asmat Motifs into Contemporary Choreography : Ukiran Menari: Transformasi Intermedial Motif Asmat ke dalam Koreografi Kontemporer - Muhammad Murda; Fachry Destyanto Matlawa (Universitas Negeri Surabaya, 2026)
Wood carvings in Asmat are not only a visual art but also a medium of memory, ancestry, and expression of cultural identity. However, many young generations are increasingly alienated from this heritage. This research investigates Sculpting Menari (Sculpting Kayu Menari), a choreographic work that takes the motif of Asmat wood carving as the inspiration for the source of contemporary movements. Qualitative practice research with flexible guidance of exploration, improvisation, and Hawkins formation phases based on the studio process was used in this study. Research has concentrated on Kaweinak motifs and the types of animals that repeatedly appear in Asmat carvings. In constructing movement, dancers do not follow the form literally but respond to the quality of the movement of load, tension, rhythm, and structure. The results showed that the adaptation of Adi's traditional movements with the chosen hip-hop techniques, especially robotics and popping, gave rise to a movement quality that felt strong, angular, and segmented. In the formation of the group, the interdependence of the dancers becomes the center of the choreography and reflects the principle of Ja Amanam Apcamar from Asmat (Strong If Together). This research implies that choreography is able to reactivate cultural knowledge through contemporary representational portraits.